Data monitoring committees for pragmatic clinical trials. (October 2015) - Ellenberg, Susan S; Culbertson, Richard; Gillen, Daniel L; Goodman, Steven; Schrandt, Suzanne; Zirkle, Maryan
In any clinical trial, it is essential to monitor the accumulating data to be sure that the trial continues to be safe for participants and that the trial is being conducted properly. Data monitoring committees, independent expert panels who undertake regular reviews of the data as the trial progresses, serve an important role in safeguarding the interests of research participants and ensuring trial integrity in many trials. Many pragmatic clinical trials, which aim to inform healthcare decisions by comparing alternate interventions in heterogeneous healthcare delivery settings, will warrant review by an independent data monitoring committee due to their potential impact on clinical practice. However, the very features that make a trial "pragmatic" may pose challenges in terms of which aspects of a trial to monitor and when it is appropriate for a data monitoring committee to intervene. Using the Pragmatic-Explanatory Continuum Indicator Summary tool that draws distinctions between pragmatic and explanatory clinical trials, we review characteristics of pragmatic clinical trials that may have implications for data monitoring committees and interim monitoring plans. These include broad eligibility criteria, a focus on subjective patient-centered outcomes, and in some cases a lack of standardized follow-up procedures across study sites. Additionally, protocol adherence is often purposefully not addressed in pragmatic trials in order to accurately represent the clinical practice setting and maintain practicability of implementation; there are differing viewpoints as to whether adherence should be assessed and acted upon by data monitoring committees in these trials. Some other issues not specifically related to the Pragmatic-Explanatory Continuum Indicator Summary criteria may also merit special consideration in pragmatic trials. Thresholds for early termination of a pragmatic clinical trial might be controversial. The distinguishing features of pragmatic clinical trials require careful consideration when developing interim data monitoring plans, and trial sponsors, investigators, and data monitoring committees should agree on a plan before trial inception. Finally, special expertise, such as an informatics, may be helpful on data monitoring committees for some pragmatic clinical trials. Patient representatives may provide particularly valuable insights in the monitoring process.